The Effects of Dairy Consumption on Vaccine Immune Response and Immunoglobulins: A Systematic Literature Review - Mina Suh; Meghan Mitchell; Naushin Hooda; Lauren C. Bylsma; Sarah S. Cohen (International Journal of Nutrition, 2024)
Public health interest in vaccinations and immune protection has increased with the COVID-19 pandemic. Dairy products are an important source of protein and other nutrients, and there are unresolved research questions regarding the potential health impact of dairy products on the enhancement of immune response. A systematic literature review was conducted to synthesize the published literature reporting the effects of dairy interventions on: 1) the vaccine-specific immune response and 2) immunoglobulins in the absence of vaccination. To assess study validity and quality, we used the Academy of Nutrition and Dietetics Quality Criteria Checklist. Sixty-one studies (59 clinical trials, 1 cohort, 1 cross-sectional survey) were included, spanning 1983-2017. Ten trials evaluated the effect of dairy intervention on vaccine-specific IgG, IgA, IgM, vaccine-specific antibody titers, seroprotection rates, or seroconversion rates. Of these, 7 reported significant increases with dairy interventions for post-vaccine tetanus antibodies, mean change in tetanus antibody level, total antibody titers to flagellin from Salmonella Adelaide, mean antibody titers to influenza B, influenza-specific IgA and IgG levels, and seroconversion or seroprotection rates for influenza A and B. Fifty-six studies evaluated dairy’s effects on immunoglobulins without vaccinations. The results were heterogenous, with some studies reporting significant enhancement of immunoglobulins (IgA, IgE, or IgG), while others observed no differences between groups. Clinical relevance of the immunoglobulin changes was not investigated in these studies. Dairy products and their components could enhance the efficacy of vaccines. This review highlights the evidence gaps and provides a potential roadmap for additional research.
Keywords: Dairy